2020
DOI: 10.3390/biom10030472
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mutant p53 in the Non-Coding RNA World

Abstract: Long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), micro RNAs (miRNAs), and extracellular RNAs (exRNAs) are new groups of RNAs with regulation activities that have low or no protein-coding ability. Emerging evidence suggests that deregulated expression of these non-coding RNAs is associated with the induction and progression of diverse tumors throughout epigenetic, transcriptional, and post-transcriptional modifications. A consistent number of non-coding RNAs (ncRNAs) has been shown to be regulated by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 103 publications
(207 reference statements)
0
23
0
Order By: Relevance
“…Mutant p53 in conjunction with the YAP/TEAD transcription-competent complex is involved in an upregulation of a circular form of oncogenic PVT1 [253]. The currently known interrelations of mutant p53 with several oncogenic ncRNAs are representative examples of a still limited but rapidly expanding knowledge of the interplay of the main driver oncoproteins with ncRNAs [254]. This knowledge will surely grow significantly in the nearby future as over 30 thousand lncRNAs alone are found in a typical human transcriptome.…”
Section: Non-coding Rnas (Micro Rnas and Long Non-codong Rnas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant p53 in conjunction with the YAP/TEAD transcription-competent complex is involved in an upregulation of a circular form of oncogenic PVT1 [253]. The currently known interrelations of mutant p53 with several oncogenic ncRNAs are representative examples of a still limited but rapidly expanding knowledge of the interplay of the main driver oncoproteins with ncRNAs [254]. This knowledge will surely grow significantly in the nearby future as over 30 thousand lncRNAs alone are found in a typical human transcriptome.…”
Section: Non-coding Rnas (Micro Rnas and Long Non-codong Rnas)mentioning
confidence: 99%
“…Noticing that broader mechanisms of ncRNA deregulation in cancer are crossing over to other targetable oncogenic pathways could help in making the ncRNA targeting more robust. For example, the mentioned CMYC or mutant p53 effects on the activity and maturation of wide miRNA populations [252,254] can be theoretically co-targeted along with selected oncomiRs.…”
Section: Non-coding Rnas (Micro Rnas and Long Non-codong Rnas)mentioning
confidence: 99%
“…Mutp53 interacts with many different proteins other than transcription factors, including tumor suppressors and oncogenic proteins, to affect their functions. Additionally, mutp53 regulates expression of many noncoding RNAs, including microRNAs (miRNAs), circular RNAs (circRNAs), and long noncoding RNAs (lncRNA), to exert its GOF activities ( Liu et al., 2017a ; Di Agostino, 2020 ). In this review, we summarize recent advances in studies on mutp53 GOF in cancer and mutp53-targeted cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus of great interest that we show that the role of YAP1 as an upstream transcriptional regulator of RPL23, at least in part, are mediated by the regulation of RPL23 expression in HeLa cells. The p53 mutation, which loses tumor suppressive functions and gains tumor-promoting activities (79), was reported to be associated with aggressive growth and increased recurrence rates for certain tumors (80). Here, we showed that RPL23 increased the expression of mutant p53 in HeLa cells.…”
Section: Discussionmentioning
confidence: 56%